Functional properties of sweet potato flour - Rubiano, Anabell M.; Galvez, Flor Crisanta F. (1995.)
Sweet potato flour (SPF) was prepared during the method of the Food and Nutrition Research Institute (FNRI). Hydration, surface-active and rheological properties of the prepared flour were determined and compared with those of all-purpose flour (APF). The SPF was utilized in empanada at different levels of substitution (0, 10, 20, 30, 40, 50%) of APF. SPF was found insoluble in water, did not foam, but was capable of forming a dough. It has 110% water absorption capacity, 71.61% fat absorption capacity, 100.90% emulsion stability at low temperature, and exhibited 14% gelation. Results likewise indicated that APF may be substituted with up to 20% SPF in empanada without significantly affecting its sensory properties and acceptance by consumers.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Flour; Sweet potato flour